RELATIONSHIP BETWEEN DIABETES AND COVID-19 SEVERITY IN PATIENTS TREATED AT SAN VICENTE DE PAUL HOSPITAL, JULY 2020 - MARCH 2021 (La U Investiga, 2022)
In Ecuador, diabetes has a prevalence of 8.5%. However, as of 2019, with the emergence of a new viral disease, it once again took center stage, since this virus affected certain vulnerable groups in a more serious and lethal way, including diabetics, increasing their hospital stay, ICU admission, need for ventilation and death. In this context, the objective of this research is to correlate diabetes and COVID 19 severity in patients treated at San Vicente de Paul hospital. The methodology is retrospective quantitative, in the period of July 2020 - March 2021, collection of data from patients' clinical history in an Excel database, data processing in SPSS using chi-square tests (Pearson and Fisher) to correlation variables, and use of absolute frequencies. Results: 64% of diabetics developed the severe disease, 48% of non-diabetics had moderate COVID, young adults had moderate COVID (46%), while older adults had severe COVID (48%). People with no pathological history tend to develop moderate (50%) and mild (33%) COVID, while people with two or more pathologies have severe disease (66%). It's concluded that there is a strong association between diabetes with a severe and critical disease of COVID 19, the social characteristics are weakly or not related, while the clinical aspects have a very significant statistical association.
Keywords: SARS-CoV-2; COVID 19; Severity level; Correlation; Diabetes mellitus